Cooperative Communication: A Review - Katiyar, Himanshu; Rastogi, Ashutosh; Agarwal, Rupali (Technical review - IETE, 2011)
The next generation wireless systems are supposed to handle high data rate as well as large coverage area. It should consume less power and utilize bandwidth efficiently. At the same time, the mobile terminals must be simple, cheap, and smaller in size. In wireless environment, the quality of received signal level degraded due to path-loss and shadowing from various obstacles in propagation path. In addition to this, signal quality suffers from fading due to constructive and destructive interference of multi-path components which makes it difficult for the receiver to extract the message correctly. Effect of fading can be suppressed by diversity technique in which replicas of signal is provided to the receiver. Receiver can make a decision on behalf of these replicas; hence, reliability of reception can be improved. Diversity can be achieved with the help of multi-antenna system where multiple antennas are installed at transmitter/receiver. However, implementing multiple antennas at wireless terminal is not practical due to size, cost, and weight constraints. Recently, cooperation among nodes has been the subject of great interest among the research community because it creates spatial diversity in wireless network, even if individual nodes do not use antenna arrays for transmis sion and reception. Here, achieved diversity gains can be translated into robustness against fading for same transmit power or substantially reduced transmitted power for same level of performance. In this paper, we discussed the state of art of cooperative communication.